Is tobacco advertising ethical or unethical? : A cross cultural research between Germany and Russia. - Wüst, Sara Denise; Lhotáková, Markéta, 1971-; Halík, Jaroslav, 1961-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
This thesis deals with the ethical attitude of Germans and Russians towards tobacco advertisement. The aim is to find out how both nationalities think about it and if it is reasonable to market tobacco products in an ethical way or not. Furthermore, this paper strives to find out if it is difficult to set boundaries between which products are harmful and which ones are not. Secondary research as well as a primary research, including quantitative and qualitative analysis, contribute to the aim of this paper and in the end, these analysis lead to the result, that neither Germans nor Russians see tobacco advertisement as ethical and that it is hard to set boundaries among some controversial products.
Vedoucí práce: Markéta Lhotáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses